COMPARATIVE METABOLITE PROFILING OF TWO WHEAT GENOTYPES AS AFFECTED BY NITROGEN STRESS AT SEEDLING STAGE - F. U. Khan; D. Fuentes; R. Threthowan; F. Mohammad; M. Ahmad (Journal of Animal and Plant Sciences, 2019)
Increasing demands for wheat productivity together with environmental concerns about the use of nitrogen-based fertilizers dictate the importance of improving nitrogen use efficiency (NUE). Identifying biological processes responsible for efficient fertilizer use will provide tools for crop improvement under reduced nutrient inputs. Metabolic response under nitrogen (N) stress was investigated at Centre for Carbon, Water and Food (CCWF), The University of Sydney, Australia. GC-MS and LC-MS techniques were used for metabolite and amino acid profiling in N-stress tolerant (Krichauff) and sensitive (Berkut) varieties under with (normal) and without nitrogen (stress) conditions in 28 days old seedlings. Twenty-six metabolites including organic acids, sugars, and amino acids were characterized in both genotypes under stress and normal conditions. Organic acids (citric acid and oxalic acid) and sugars (glucose, sucrose, fructose and mannose) were significantly increased in both varieties under stress conditions, whereas, malic and oxalic acids were increased in tolerant (Krichauff), while decreased in susceptible (Berkut) genotype. Sugar alcohol (pentaerythitol, xylitol and myo-inositol) remained similar in both genotypes under stress and normal conditions. Seven out of twenty amino acids (glycine, cysteine, valine, methionine, isoleucine, leucine and tryptophan) were not detected in both genotypes under both stress and normal conditions. Most of the remaining amino acids were detected under normal condition only, exhibiting the relationship of amino acid with nitrogen applications. Amino acids viz. serine, aspargine, alanine, threonine, glutamine and proline were specifically decreased under stress condition in Krichauff, whereas glutamic acid increases in both genotypes under stress than normal conditions. Compared with Berkut, Krichauff experienced greater increase in both sugars and organic acids, and more pronounced decrease in most of the amino acids under stress condition. L-ascorbic acid, allo-insitol, lysine and tyrosine were unique metabolites found only in tolerant (Krichauff) genotype. Metabolic responses of wheat to nitrogen stress were dynamic and involve many metabolites. Greater N-tolerance and different metabolic expression in Krichauff necessitate further studies to examine various pathways and adaptive reactions at critical stress conditions. Current findings of metabolite profiling might help in unveiling the genetic targets for the improvement of nitrogen use efficiency in wheat.
Keywords: N/A